(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
A field method research linguistic unit on the ethnoculchure background, to permit investigate linguistic system in her intergrity and establishment contact between vocabulary, what her to form. Article to scrutinize lexuco-sementic field «Liquid» with position ethnoculchure Ukrainian people.